Understanding the impact of the COVID-19 pandemic on refugee communities in San Diego, California: A participatory action research cross-sectional study - Lotus McDougal; Jeanine Erikat; Homayra Yusufi; Ramla Sahid; Samantha Streuli; Rebecca Fielding-Miller (Elsevier, 2022)
Background: While the COVID-19 pandemic has impacted people worldwide, refugee communities are particularly vulnerable to the pandemic's social, economic and health impacts. This study assessed factors associated with increases in adverse community effects of COVID-19 in a refugee community in California. Methods: This study uses data from a cross-sectional survey developed and administered as part of a participatory action research project by a refugee community organization in San Diego, California. Data was collected between September and November 2020 in a sample of refugee community members (n = 517). Multivariable Poisson regression models measured associations between sociodemographic and acculturation measures with seven adverse community effects overall and stratified by duration of residence in the United States. Adverse community effects included job/wage loss, bank/cash access barriers, food insecurity, school interruptions, household violence, substance misuse and poor mental health. Results: Refugee community members reported an average of 2.1 adverse community effects that worsened during the COVID-19 pandemic, with job/wage loss and poor mental health the most prevalent (84% and 49%). Characteristics associated with reporting increased numbers of adverse community effects included being younger, female, childless, not actively seeking employment, living in the US for six or more years and speaking English at home. Stratified analyses show that these associations were concentrated in refugees who had lived in the US for at least six years. Conclusion: Refugee communities have experienced pervasive job losses and worsening mental health during the COVID-19 pandemic, and these effects are concentrated in respondents who have lived in the US for six or more years. Additional targeted support is needed to ensure that refugees who have lived in the US for longer durations have the financial and social support needed to cope with the unprecedented challenges brought on by the COVID-19 pandemic.